A non-destructive approach using MatLab software for morphology analysis of ancient mural deterioration. (3rd October 2017) - Zhang, Yidong; Wang, Julin; Liu, Hongli; Wang, Xudong
Abstract : The murals in Dunhuang Grottoes, a famous world cultural heritage site, are precious and unique, so research on mural surface changes and evaluation of the degree of deterioration should be non-destructive. In this study, tracking photographs of a simulated mural surface were processed with MatLab software to obtain a three-dimensional image and Z axis data, and a calculation method for quantitative analysis was also proposed. The feasibility of this approach was confirmed by simulated experiments of mural damage in the laboratory and analysis of real murals in situ. It was also applied to analysis of surface deterioration of an earthen archaeological site before and after rainfall erosion. As a simple and non-destructive approach, it could be used for the analysis of micro changes in murals or for monitoring real time surface changes at cultural heritage sites.